Development of a Biodiversity Indicator for LCA - (:unkn) unknown (My University, 2026)
·        We propose a full literature review of the existing impact pathways in Life Cycle Impact Assessment that evaluate the environmental damage exerted in terms of biodiversity loss, both in aquatic and terrestrial compartments, and analyze to what ex